1999
DOI: 10.1126/science.284.5421.1805
|View full text |Cite
|
Sign up to set email alerts
|

Importance of AMPA Receptors for Hippocampal Synaptic Plasticity But Not for Spatial Learning

Abstract: Gene-targeted mice lacking the L-alpha-amino-3-hydroxy-5-methylisoxazole-4-propionate (AMPA) receptor subunit GluR-A exhibited normal development, life expectancy, and fine structure of neuronal dendrites and synapses. In hippocampal CA1 pyramidal neurons, GluR-A-/- mice showed a reduction in functional AMPA receptors, with the remaining receptors preferentially targeted to synapses. Thus, the CA1 soma-patch currents were strongly reduced, but glutamatergic synaptic currents were unaltered; and evoked dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

67
732
9
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 730 publications
(810 citation statements)
references
References 48 publications
67
732
9
2
Order By: Relevance
“…In the hippocampus, LTP is dependent on increased insertion of the AMPA receptor subunit, GluR1 (Shi et al, 1999;Zamanillo et al, 1999). Previous studies found no detectable changes in the VTA in total cellular protein levels of GluR1 between cocaine-and saline-treated mice (Ungless et al, 2001).…”
Section: Resultsmentioning
confidence: 96%
“…In the hippocampus, LTP is dependent on increased insertion of the AMPA receptor subunit, GluR1 (Shi et al, 1999;Zamanillo et al, 1999). Previous studies found no detectable changes in the VTA in total cellular protein levels of GluR1 between cocaine-and saline-treated mice (Ungless et al, 2001).…”
Section: Resultsmentioning
confidence: 96%
“…For instance, Mayford et al (1996) showed in a learning task that the blockage of LTP in the hippocampus leads to a worse task performance compared to control. However, in a quite similar experimental setup the blockage of LTP leads to no significant differences (Zamanillo 1999). Regarding the neural correlate of memory, potential memory items were found, for example, in songbirds during song and recapitulation as stereotypical sequences of spike burst (Hahnloser et al 2002) or during a spatial task, as spatiotemporal patterns (Harris et al 2003) in the hippocampus.…”
Section: Links Between Time Scales Of Memory and Physiologymentioning
confidence: 90%
“…GluA1 is dominant in activity-dependent recruitment of AMPARs to synapses. This is mediated by CaMKII phosphorylation of GluA1 and interaction with synaptic PDZ domaincontaining proteins that recruit and retain GluA1/GluA2 AMPARs at synapses during induction of long-term potentiation (LTP) 15,16 . Once the GluA1-mediated increase in AMPAR number is established, interactions with GluA2 take over to control constitutive and activity-dependent AMPAR endocytosis, and long-term depression (LTD) 10,17 .…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%